Autoconsciência como uma variável de pesquisa : teoria e mensuração - Echevarria, Daniel Rodrigues (2016)
In this thesis a review of the self-awareness theories and instruments is used to reflect on the role of various forms of access to the phenomenon and how different levels of evidence may help build an articulated understanding of self-awareness. An attempt is made to contribute to the toolset available for investigation in the field through the adaptation of a selfawareness self-report scale. Article 1 consists of a thematic study of the self-awareness literature, from classical and analytical philosophers and early authors in psychology, to the historic disinterest in the field following the ascension of behaviorism, and the renewed interest in experimental manipulation and measurement of self-awareness in the 1970s and on, to the reappearance of multi-level models of self-awareness in the last 15 years. Article 2 consists of the translation and adaptation of the Situational Self Awareness-Scale for Brazilian adults, examining evidences of validity through exploratory factor analysis, concurrent validity comparisons with self-consciousness scales and test-retest reliability. Further exploratory and pilot studies are reported in the form of notes from the field.